Peningkatan Kapasitas Desa Tangguh Bencana - Rina Suryani Oktari (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
Lam Teungoh village is one of the most affected areas during the tsunami 2004. Twelve years after the tsunami, most of the tsunami preparedness facilities in Lam Teungoh Village, such as evacuation signs and information on tsunami hazards are found in poor conditions. This activity aims to improve the capacity and resilience of apparatus and community of Lam Teungoh Village in the facing disaster. This activity is carried out through participatory survey methods, lectures, discussions, simulation, observation, mentoring, and evaluation. This activity involves several partners including Aceh Besar District Disaster Management Agency, village and community governments, schools, and non-governmental organizations (NGOs). The outcomes of this activity include: i) Increased community understanding on disaster management, ii) Hazards, vulnerabilities, and capacities of Lam Teungoh Village on facing disaster are identified, iii) Disaster Management Plan Document, Disaster Risk Map, and Disaster Evacuation Map are formulated, iv) Disaster Risk Reduction Forum in Lam Teungoh Village is established, and v) Training needs of women and youth group in improving community economic status are identified.